2005
DOI: 10.1128/jvi.79.10.6349-6357.2005
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of Hepatitis C Virus Genotypes between Plasma and Peripheral Blood Mononuclear Cells

Abstract: Differences in hepatitis C virus (HCV) variants of the highly conserved 5 untranslated region (UTR) have been observed between plasma and peripheral blood mononuclear cells (PBMC). The prevalence and the mechanisms of this compartmentalization are unknown. Plasma and PBMC HCV variants were compared by single-strand conformation polymorphism (SSCP) and by cloning or by genotyping with a line probe assay (LiPA) in 116 chronically infected patients, including 44 liver transplant recipients. SSCP patterns differed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 42 publications
(52 reference statements)
7
142
0
2
Order By: Relevance
“…[79][80][81] While some of these data should be viewed cautiously, as a variety of techniques were utilized and a limited number of samples [82][83][84] Interestingly, sequence analysis has subsequently revealed that certain viral variants may be selected for growth in extrahepatic cell types, implying that HCV diversity directly impacts cell tropism. 85,86 Furthermore, several studies have described a non-random distribution of HCV sequences in hepatic and extrahepatic compartments, 72,[87][88][89][90][91][92][93][94][95][96] leading to the conclusion that the presence of tissue-specific sequences is compatible with independent viral replication in extrahepatic sites. It has also been speculated that HCV variants within distinct compartments may differ in their sensitivity to interferon, although this hypothesis has not been formally tested.…”
Section: Evidence For Extrahepatic Replication Of Hcvmentioning
confidence: 99%
“…[79][80][81] While some of these data should be viewed cautiously, as a variety of techniques were utilized and a limited number of samples [82][83][84] Interestingly, sequence analysis has subsequently revealed that certain viral variants may be selected for growth in extrahepatic cell types, implying that HCV diversity directly impacts cell tropism. 85,86 Furthermore, several studies have described a non-random distribution of HCV sequences in hepatic and extrahepatic compartments, 72,[87][88][89][90][91][92][93][94][95][96] leading to the conclusion that the presence of tissue-specific sequences is compatible with independent viral replication in extrahepatic sites. It has also been speculated that HCV variants within distinct compartments may differ in their sensitivity to interferon, although this hypothesis has not been formally tested.…”
Section: Evidence For Extrahepatic Replication Of Hcvmentioning
confidence: 99%
“…The presence of negative-strand RNA in PBMCs from infected patients has been demonstrated (Ducoulombier et al, 2004;Lanford et al, 1995;Laskus et al, 2000;Lerat et al, 2000;Moldvay et al, 1994) which suggests the existence of a potentially important extrahepatic site of HCV replication (Bain et al, 2001;Laporte et al, 2003;Roque Afonso et al, 1999;Roque-Afonso et al, 2005). Many viruses possess strategies for evading or limiting the interferon-induced antiviral response and lead to progression of a disease.…”
Section: Discussionmentioning
confidence: 99%
“…Compartmentalization between different tissues of the same patient (serum-brain, serumsaliva, serum-peripheral blood mononuclear cells) was described in several studies (Radkowski et al, 2002;Roque Afonso et al, 2005). Furthermore, the existence of different genotypes and/or viral variants in different tissues of the same patient has been also demonstrated (Radkowski et al, 2002;Roy et al, 1998) and particularly, peripheral blood mononuclear cells can harbor distinct HCV variants that are not detected in plasma samples (Di Liberto et al, 2006, Roque-Afonso et al, 2005; adding a potential complication to the assessment of the correct HCV genotype.…”
Section: Different Genotypes In Different Reservoirsmentioning
confidence: 99%
“…Although peripheral blood mononuclear cells (PBMC) are not the primary site of HCV replication, previous reports emphasize their role as viral reservoirs (Radkowski et al, 2005;Pham et al, 2004). Furthermore, different genotypes have been reported both in plasma and PBMC (Roque Afonso et al, 2005) and it has also been speculated that extrahepatic HCV diversity may be an important determinant of treatment response (Blackard et al, 2007). The final purpose of our study was to investigate the existence of unapparent HCV mixed infections in the hemophilic population in Argentina, analyzing the HCV genotypes detected in plasma or serum samples and comparing them to viral strains emerging under long-term PBMC cultures.…”
Section: Hcv Mixed-genotype Infections In a Population With Hemophilimentioning
confidence: 99%
See 1 more Smart Citation